You can, you will : 8 undeniable qualities of a winner - Osteen, Joel (Faith Words, 2014)
Joel Osteen shares eight undeniable qualities of winners that can help you to reach your potential and achieve new levels of success in your life. You are created to be a winner. Get these eight principles deep down on the inside and boldly go in the direction of your destiny. Keep Your Vision in Front of You: Dare to dream big dreams. Run Your Race: Focus on your unique course and goals. Expect Good Things: Anticipate great opportunities. Have a Positive Mind-set: Take control of your thoughts and attitudes. Commit to Excellence: Do your best and maintain high standards. Keep Growing: Be proactive, be intentional, build on your gifts, and continually improve. Serve Others: Invest yourself in others. Stay Passionate: Light the fire within and approach life with enthusiasm.